Inspection Scheme of Coal Mine Belt Conveyor Based on UAV Technology - LI Biao (Meikuang Anquan, 2020)
This paper designs a long-distance inspection scheme of coal mine belt conveyor based on UAV, which is applied in the inspection of coal mine belt conveyor transportation system. This paper introduces the overall scheme of UAV patrol inspection, discusses the UAV body design, UAV navigation design, UAV obstacle avoidance design, charging pile design, flight scheme design and the corresponding working principle, and determines the feasibility of the scheme through prototype production and field test flight.